(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Spherical ordered mesoporous silica particles with radially oriented mesopores were successfully prepared by using non-ionic amphiphilic di-block co-polymers CnH2n+1-(EO)x-OH as template and tetraorthosilicate (TEOS) as silica precursor. The synthesized mesoporous silica materials were characterized by XRD, N2 adsorption-desorption and SEM techniques. CO2 adsorption at 0 Â°C was evaluated by a volumetric method, and the CO2 sorption behavior was described by applying both Langmuir and Freundlich equations. Results indicate a high adsorption capacity of CO2 (5-9 mmol/g), depending essentially on the porous texture of the materials. An adsorption kinetic model was proposed to describe the adsorption of CO2 over template-free mesoporous siliceous materials. A good agreement with experimental data was found.